Health Promotion in Children and Adolescents through Sport and Physical Activities - Bianco, Antonino (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
I made the important decision to manage a Special Issue, because I believe it to be extremely important to focus on children's and adolescents' physiological and psychological development. I aimed to collect research that investigates the role of physical activity and sport on physical and mental well-being, with a particular focus on practical implications, innovation, tools, and technique. This Special Issue, "Health Promotion in Children and Adolescents through Sport and Physical Activities" addresses pediatric exercise science as a key scientific discipline able to help future generations live longer and better. It is already clear that sedentariness and a low level of muscular strength and power significantly affects cognitive functions and daily relations, but it is interesting to understand the key determinants and how we can help practitioners better manage these concerns in their patients. Authors were invited to submit letters, original research papers, case studies, meta-analyses, and systematic reviews.